In situ U–Pb age determination of apatite from carbonatite and kimberlite in the Batain Basin, eastern Oman - Sun, Jing; Jiang, Leiyin; Sun, Jiaxuan (Frontiers in Earth Science, 2023)
Northeastern Oman is characterized by carbonatite and kimberlite complexes, which are the ideal samples for studying the relationship between carbonatite and kimberlite. However, the ages of the Oman kimberlite and carbonatite complexes are still unknown, which restricts the understanding of the relationship between carbonatite and kimberlite in Oman. In this study, we use in situ laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS) to analyze the apatite from Oman carbonatite, kimberlite, and spessartite. The U–Pb apatite ages are 141.6 ± 6.0 Ma, 137.4 ± 5.2 Ma, and 141.2 ± 6.2 Ma for carbonatite, spessartite (a kind of calc-alkaline lamprophyre), and kimberlite, respectively. These results suggest that the carbonatite and kimberlite were emplaced contemporaneously, followed by calc-alkaline carbonatite (spessartite) emplaced in the Early Cretaceous. The occurrence of carbonatite, kimberlite, and spessartite magmatism of Oman was contemporaneous with the time of the Gondwana breakup during the opening of the Indian Ocean. It is seen that 140 Ma–130 Ma is one of the strongest global kimberlite abundance peaks of the 250 Ma–50 Ma kimberlite bloom, which corresponds with the period of the Pangea supercontinent breakup. The Oman kimberlites and carbonatites are related to a distal effect of the breakup of the Gondwana portion of the Pangea supercontinent, which provided a cool, volatile-fluxed decompression-related circumstance for the formation.